Malarska koncepcja w eseju filozoficznym Bolesława Micińskiego - Koźbiał, Natasza (Zagadnienia Rodzajów Literackich, 2022)
The article discusses the essayistic work of Bolesław Miciński, who was interested in the individualization of the form of expression, both in the sphere of content and form. Contemporary thinking about philosophy in neo-positivist terms prompted the writer to create an individual dictionary of concepts that frees philosophy from rigorous frameworks and specialized jargon. In a modern, philosophical essay, he realizes a free reflection on aesthetic, philosophical, social and political issues (the relationship between art and politics). The authoress interprets the painting concept in Portret Kanta, remaining within the tricks and concepts used by the writer. The analysis of the creation of a philosophical and literary portrait, presented in the form of an essay, makes it possible to highlight the problems that the writer deals with — the issue of the existence of time in painting or the possibility of transposing concepts into images (utpictura poesis). From a polemic with the 18th-century aesthetic — Gotthold Ephraim Lessing — the authoress moves to the notion of “fugue” as a potential realization of space in music, which the writer mentioned in Podróże do piekieł. Moreover, he considers the form of a fugue in reference to classicism in literature. This sketch is an initial attempt to unravel the “hidden, significant knots” in the work of the interwar essayist.